Cerebellar Medulloblastoma in Middle-to-Late Adulthood - Majid Aljoghaiman; Mahmoud S. Taha; Marwah M. Abdulkader (Hindawi Limited, 2018)
Medulloblastoma is a malignant brain tumor that is typically seen in children. It is classified as an embryonal tumor, classically located within the posterior fossa. When it involves the fourth ventricle, the patient commonly presents with signs and symptoms of raised intracranial pressure secondary to obstructive hydrocephalus. It is exceedingly rare for Medulloblastoma to occur in middle and late adulthood. In this paper, we present a case of a 51-year-old man who presented with a posterior fossa mass that was diagnosed later as Medulloblastoma.